Signifikansi Konseling Pastoral Sebagai Upaya Meningkatkan Kecerdasan Spiritual Generasi Z Kristen: Pembinaan Warga Gereja - Rakai Ranu Pranasoma (ILLUMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2021)
During its development, generation Z Christians experience moral decadence because they want to fulfill their own interests. in various ways they try to have their wishes fulfilled and they unwittingly neglect their spiritual growth. This also cannot be separated from the attention of the church to provide guidance for generation Z Christians and to grow the efficiency of the church in the world. Departing from these facts, this research was made to become a guide for practitioners of guiding church members in increasing the spiritual intelligence of generation Z Christians through pastoral counseling. The method used in this research is a qualitative approach with literature studies obtained from print and electronic sources. From this research, it is found the important role of pastoral counseling which is very effective to be applied for the formation of Z Christian generation. This result is supported by the efforts made in pastoral counseling of generation Z Christians, which are not coercive and do not create dependence on others in increasing their spiritual intelligence. Therefore, the church needs to seek pastoral counseling to increase the spiritual intelligence of Generation Z Christians in the congregation.